A perspective: Regeneration of soft and hard tissues in the oral cavity, from research to clinical practice - Puterman, Israel; Fien, Matthew J.; Mesquida, Juan; Ginebreda, Ignacio; Bauza, Guillermo; Somerman, Martha (Frontiers in Dental Medicine, 2023)
Regenerative medicine has gained much attention and has been a hot topic in all medical fields since its inception, and dentistry is no exception. However, innovations and developments in basic research are sometimes disconnected from daily clinical practice. This existing gap between basic research and clinical practice can only be addressed with improved communication between clinicians, academicians, industry, and researchers to facilitate the advance of evidence-based therapies and procedures and to direct research to areas of clinical need. In this perspective, six participants with strong clinical and research interests debated five previously conceived questions. These questions covered current methods and procedures for soft and hard tissue regeneration in the oral cavity with predictable outcomes, limitations of their respective protocols, and needs for future development of regenerative materials and technologies.